Influence of Fermi‐Level Engineering in Multi‐Interface CuO/Cu2O||rGO||h‐WO3||rGO|| Photoelectrodes on Photoelectrochemical CO2 Reduction. Issue 6 (11th April 2022) - Bieńkowski, Krzysztof; Małolepszy, Artur; Stobiński, Leszek; Strawski, Marcin; Wróbel, Piotr; Solarska, Renata
Abstract : Heterojunction engineering enables more versatile and higher performance systems than single components. In parallel with heterojunction engineering, defect engineering has emerged as a means of tailoring the optoelectronic properties of photoelectrodes. However, constructing effective and stable hybrid semiconductor heterojunctions is a challenging task under the strict requirements of band alignment, vacancy characteristics, and interface properties. Herein, the photoelectrochemical (PEC) reduction of CO2 to methanol is augmented by a novel approach explored by modeling the Fermi level in a multi‐interface architecture. The excellent PEC CO2 reduction activity is attributed to the formation of a high‐performance, energetically aligned multi‐interface system of CuO/Cu2 O||rGO| h ‐WO3 |rGO (rGO = reduced graphene oxide layer). The overall performance of this hybrid, system strongly depends on the number of oxygen groups in rGO and the structural properties of rGO. Therefore, to construct an effective PEC system, numerous postsynthetic treatments are explored for their practicality and usefulness. The results reported herein clearly show that the best performance toward the CO2 photoreduction currents of 3 mA/cm 2 at 0.00.1 V versus reversable hydrogen electrode (more than double that of the CuO/Cu2 O system) has been reached for the semiconductor architecture containing two layers of rGO. Abstract : The enhanced photoelectrochemical (PEC) CO2 reduction performance is investigated by step‐by‐step multiinterface structure optimization, followed by band energetics alignment in CuO/Cu2 O||rGO| h ‐WO3 |rGO. Therefore, numerous postsynthetic treatments and geometries are explored for their usefulness for solar CO2 conversion to fuels. The findings provide an explanation for the nature of CO2 activation and relationship between its stability and other structural and spectral properties.